Message from the Editor (s) - Abd Wahab, Mohd Helmy; Wan Ishak, Wan Hussain; Ab Bakar, Juhaida; Sudin, Nor’aisah; Packeer Mohamad, Shafinah Farvin; Noradila Nordin; Mohamad Farhan Mohamad Mohsin (Multidisciplinary Applied Research and Innovation, 2023)
The editorial team welcomes all readers to our 2nd issue of proceeding of Innovative Research, Invention and Application Exhibition (I-RIA 2022) which was held virtually on 9 August 2022 at Universiti Utara Malaysia, Malaysia. The theme of this year is “Humanizing Today’s Technology for Resilient Future”. This proceeding consists of broad spectrum innovation papers within Internet-of-Things, Social Informatics, Application and multimedia services, Blockchain, Technology in education, Smart Device Design, Health Informatics and Technology, Network and Communication Technology, Pandemic Innovation, Data Science/Analytics, Cybersecurity, Green Technology and other topics in Science and Technology. All innovation papers in this issue were peer-reviewed, ranging from concept idea and up to applications level. Special thanks to all authors who had contributed their manuscript and presented and showcased their innovative projects during the stipulated sessions. In addition, special thanks to the I-RIA 2022 editorial team for their tremendous works and continuous effort in publishing this issue. We also would like to express our sincere appreciation to the international editorial advisory board and the selected reviewers for their valuable comments and suggestions to ensure the quality of the research paper published in this issue. The I-RIA2022 issues will be a good platform for exhibitor in the schools, higher institutions and the industries to disseminate their latest findings and discoveries. Last but not least, we also would like to ensure the continuity of the next issues, thus we look forward to receive scholarly written articles from innovators around the world during our next event. I-RIA2022 Editorial team